Effects of Different Adjuvants on the Growth and Sporulation of the Entomopathogenic Fungus, Metarhizium anisopliae (METSCH) - Sasidharan, T. O.; Sapna Bai, N.; Remadevi, O. K.; Balachander, M.; Dharmarajan, Priyadarsanan (Indian Forester, 2014)
Assessment of the effect of formulation components on viability of fungal conidia is imperative prior to their use in formulations. A range of adjuvants were evaluated for their effect on growth and sporulation of three Metarhizium isolates to identify an appropriate adjuvant for developing a liquid formulation. Oils such as neem oil, pongam oil, eucalyptus oil, SG oil, coconut oil and diesel, each at 0.1, 0.5 and 1.0% and mineral oil at 1,2,3,4&5% concentrations and surfactants such as glycerol at 0.1, 0.2, 0.5, 0.8&1.0% and tween-80 at 0.01, 0.02, 0.05&0.08% concentrations were tested to find out the most appropriate adjuvant and its optimum concentration required for making liquid formulations of Metarhizium. Even though biomass and sporulation in mineral oil formulation was slightly superior to pongam oil formulation, the insecticidal activity of pongam oil endows an added advantage for its use in formulations for controlling insect pests. The observations on biomass produced after 7 days of treatment with surfactants revealed that treatments with tween-80 at 0.08 and 0.05% and glycerol at 1.0 and 0.8% were significantly superior to untreated control.